Illusory Oscillation of the Central Rotation Axis. (July 2019) - Nakajima, Yutaka; Kakuda, Shohei; Satoh, Shunji
In this study, we report a novel visual illusion for rotational motion, in which the central rotation axis of a partially invisible (apparent) square is perceived as exhibiting oscillatory rotation. To investigate the cause of this illusion, we measured the central position of a static apparent shape using an adjustment method (Experiment 1) and manipulated the speed of the rotating apparent square to test whether the illusion could be cancelled out by counteracting rotation using a constant method (Experiment 2). The results revealed that the perceived central position of a static apparent shape was shifted toward the outside. The shifted position depended on the orientation of the stimulus, and its position was arranged as if it was moving in a circular trajectory. In addition, the cancellation technique using counteracting rotation was successful, and cancellation of faster rotation required a greater radius of counteracting rotation. These results indicated that the illusion is induced by an interaction between illusory shifts of the central position of the static shape and the summation of motion vectors or motion momentum (e.g., centrifugal force) derived from shape representation by perceptual completion.